Role of sleep quality in mediating the relationship between sexual minority status and suicidal behavior among Chinese adolescents - Huang Y; Li P; Lai Z; Jia X; Xiao D; Wang T; Guo L; Lu C (Psychology Research and Behavior Management, 2018)
Yeen Huang,1,* Pengsheng Li,1,* Zhisheng Lai,2 Xiaofei Jia,3 Di Xiao,1 Tian Wang,1 Lan Guo,2,* Ciyong Lu1,4,* 1Department of Medical Statistics and Epidemiology, School of Public Health, Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 2Department of HIV/AIDS Prevention and Control, Yuexiu District Center for Disease Control and Prevention, Guangzhou, Guangdong, People’s Republic of China; 3Department of HIV/AIDS Prevention and Control, Tianhe District Center for Disease Control and Prevention, Guangzhou, Guangdong, People’s Republic of China; 4Guangdong Provincial Key Laboratory of Food, Guangdong Engineering Technology Research Center of Nutrition Translation, Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China *These authors contributed equally to this work Background: Studies suggest that sexual minority adolescents experience higher rates of sleep disturbance than their heterosexual peers, and disturbed sleep is a well-known risk factor for suicidality. This study aimed to explore whether sleep quality had mediating effects on the relationship between sexual minority status and suicidal behavior in Chinese adolescents. Methods: We analyzed data collected from 7th to 12th graders from seven randomly selected provinces of People’s Republic of China in the 2015 School-Based Chinese Adolescents Health Survey. The 123,459 students who completed questionnaires regarding sexual attraction, the Pittsburgh Sleep Quality Index, past-year suicidal ideation, and past-year suicide attempts were included in our study (response rate: 95.9%). Results: After adjustment for covariates, sexual minority status was associated with suicidal ideation (adjusted odds ratio =1.82, 95% CI=1.69–1.95) and suicide attempts (adjusted odds ratio =2.16, 95% CI=1.82–2.56). Sleep quality partially mediated the effects of sexual minority status on suicidal ideation (standardized β estimate=0.009, 95% CI=0.007–0.012) and suicide attempts (standardized β estimate=0.004, 95% CI=0.003–0.005). Conclusion: Poor sleep quality partially explained the increased risk of suicidality for Chinese sexual minority adolescents. To prevent subsequent suicidality, suicide interventions targeting sexual minorities should be made, with a focus on their disparities in sleep disturbance and sleep health promotion. Keywords: sexual minority, suicidal behavior, adolescents, sleep quality, mediating effect